Calorie Restriction With Exercise Intervention Improves Inflammatory Response in Overweight and Obese Adults: A Systematic Review and Meta-Analysis - Liu, Yubo; Hong, Feng; Lebaka, Veeranjaneya Reddy; Mohammed, Arifullah; Ji, Lei; Zhang, Yean; Korivi, Mallikarjuna (Frontiers in Physiology, 2021)
Background/Purpose: In this systematic review and meta-analysis, we assessed the effects of exercise (EX) combined with calorie restriction (CR) intervention on inflammatory biomarkers, and correlations between biomarkers and participants’ characteristics were calculated in overweight and obese adults. Methods: An article search was conducted through PubMed, Web of Science, EMBASE, the Cochrane database, Scopus, and Google Scholar to identify articles published up to April 2021. Studies that examined the effect of EX + CR intervention on inflammatory biomarkers, including C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), and compared them with a CR trial in overweight and obese adults were included. We calculated the pooled effect by meta-analysis, identified the correlations (between inflammatory biomarkers and participants’ characteristics) through meta-regression, and explored the beneficial variable through subgroup analysis. The Cochrane risk of bias tool and Methodological Index for Non-randomized Studies were used to assess the risk of bias for the included trials. Results: A total of 23 trials, including 1196 overweight and obese adults, were included in the meta-analysis. The pooled effect showed that EX + CR intervention significantly decreased CRP levels (P = 0.02), but had no effect on IL-6 (P = 0.62) and TNF-α (P = 0.11). Meta-regression analysis showed that the effect of EX + CR on CRP, IL-6, and TNF-α changes was correlated with lifestyle behavior of adults (Coef. = −0.380, P = 0.018; Coef. = −0.359, P = 0.031; Coef. = −0.424, P = 0.041, respectively), but not with age and BMI. The subgroup analysis results revealed that participants with sedentary lifestyle behavior did not respond to EX + CR intervention, as we found no changes in CRP, IL-6, and TNF-α concentrations (P = 0.84, P = 0.16, P = 0.92, respectively). However, EX + CR intervention significantly decreased CRP (P = 0.0003; SMD = −0.39; 95%CI: −0.60 to −0.18), IL-6 (P = 0.04; SMD = −0.21; 95%CI: −0.40 to −0.01) and TNF-α (P = 0.006; SMD = −0.40, 95%CI: −0.68 to −0.12) in adults without a sedentary lifestyle or with a normal lifestyle. Furthermore, the values between sedentary and normal lifestyle subgroups were statistically significant for CRP, IL-6, and TNF-α. Conclusion: Our findings showed that combination EX + CR intervention effectively decreased CRP, IL-6, and TNF-α in overweight and obese adults with active lifestyles, but not with sedentary lifestyle behavior. We suggest that ‘lifestyle behavior’ is a considerable factor when designing new intervention programs for overweight or obese adults to improve their inflammatory response.